EXPLORING THE LINK BETWEEN SAFETY VARIABLES AND WELL-BEING OUTCOMES IN MALAYSIAN MANUFACTURING SECTOR: A CONCEPTUAL FRAMEWORK - Norizan Baba Rahim, (INTERNATIONAL JOURNAL OF INNOVATION AND INDUSTRIAL REVOLUTION (IJIREV), 2024)
In Malaysia’s manufacturing industry, workplace mishaps and injuries are a big problem. This industry has made only minor developments in terms of reducing fatalities and significant injuries. The fatality rate has decreased marginally; however, the previous year’s severe injury rate remains unchanged (Department of Occupational Safety and Health, 2021). In Malaysia’s aspiration into becoming an advanced country by 2020, reducing occupational mishaps and injuries is one of the key employments concerns it aims to address. As a substantial determinant of mishaps and safety behaviour, the perception of the work setting is considered essential. Safety measures must emphasise the way employees view their work setting in order to improve safety plans and practices. Safety policy and procedures must bring about a shift in employees’ mindsets and awareness of their immediate work setting in order to succeed in the intervention towards the shift in behaviour. This study proposes a conceptual framework to examine the interaction between safety climates, safety behaviour towards the quality of work-life, and psychological well-being within Malaysia’s manufacturing industry that would assist in the advancement of more efficient safety interventions of reducing mishaps.